Beautiful things happen when a woman trusts God - Walsh, Sheila, 1956- (Nashville, Tenn. : Thomas Nelson, 2009)
Most Christian women live with a deep sense that they can't seem to get things right, that if only they could be a little better, life would straighten out. Through her own personal hardships, Sheila Walsh has learned that the Christian life is not about getting things right or back to "normal." She writes, "Christ comes not to get us out of our difficulties but to live in us through them." She wants to show women that God has a stunningly beautiful moment of redemption for them that leads to a lifetime of peace and joy.
Why are you so afraid?: the beauty of courage -- An open door: the beauty of brokenness -- The hunger to belong: the beauty of transparency -- A broken dream becomes a beautiful life: the beauty of waiting and being in the present -- Why the pain?: the beauty of crying out to Jesus -- Into the darkness to find the light: the beauty of seeing -- The life of Christ in us: the beauty of a quiet trust -- Trusting God with your fear: the beauty of taking a step forward -- Trusting God with your dreams: the beauty of forgiving -- Is it ever too late to start again?: the beauty of a second chance -- Trusting God when you have a lot to lose: the beauty of giving your all -- Trusting God with your journey: the beauty of a pilgrim -- We're going home, into the arms of God.
Keywords: Christian women -- Religious life; Trust in God; Nonfiction